MORPHOLOGICAL CHARACTERISTICS OF GIRLS, 7-9 YEARS OF AGE, ENGAGED IN MODERN DANCING - Milan Cvetković; Boris Popović; Dušan Stupar; Aleksandra Spasić; Dejan Orlić; Slobodan Andrašić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: Selection in modern dancing, especially in the "artistic dance" style, is increasingly directed towards finding proper morphological types with exceptional motor and individual creative abilities. The aim of this paper was to determine morphological characteristics of 7-9 years old girls engaged in modern dancing for a continuous period of at least one year, as well as to compare them with the girls that have never been engaged in an organized physical activity. Methods: The aim was accomplished by using a battery of eight anthropometric tests that evaluate to a greatest extent body voluminosity and body mass as well as subcutaneous fat tissue of the test subjects as they could be affected to a greatest extent by means of physical education. Multivariate analysis of variance (MANOVA) was used for determining the quantitative differences between the systems of anthropometric variables from the two groups of respondents. For determining the difference between each individual anthropometric measure and for both age groups, an univariate analysis of variance (ANOVA) was applied. P = 0.05 was the criterion adopted for the level of statistical significance. All results have been analyzed using the software for statistical analysis SPSS 20. Results: Research results indicate a statistically significant difference in terms of a quality morphological status defined by smaller volume, body mass and lesser fat tissue at all age categories of female subjects which is in favor of girls engaged in modern dancing. According to these results the author concludes which morphological type of girls at younger school age is desirable for successful engagement in modern dancing. Discussion: By looking at the general morphological space of analyzed groups of respondents it can be concluded that the girls engaged in modern dancing, statistically significantly differ in a quantitative manner from their peers who are not involved in organized physical activity, at the most strict level of statistical inference. This difference is reflected in the higher-quality morphological status defined by lower volume, body weight, and less subcutaneous adipose tissue which lead the author to conclusion about morphological type of girls aged 7-9 years which is desirable for successful engagement in modern dancing, depending on the dance category respondents are engaged in. Generally, it can be concluded that the contents of modern dances represent a positive impact on the morphological status of girls aged 7-9 years and in particular on the dimensions responsible for the volume and mass of the body, as well as the subcutaneous adipose tissue. As such, these contents are highly recommendable for implementation in physical education, both in school and after school, by engaging in dance studios and clubs dealing with this type of dance. References: Kostić J, Zagorc M, Uzunović S (2004). Acta Universitatis Palackianae Olomucensis., Gymnica, 34 (1), 59-64. Medved R, Barbir Ž, Brdarić R, Gjurić Z, Heimer S, Kesić B, Medved V, Miheli Z, Pavišić-Medved V, Pećina M. Todorović B, Tucak A, Vuković M (1987). Sportska medicina. Zagreb: JUMENA. Popović B (2008). Glasnik Antropološkog društva Srbije, 43, 455-65, Novi Sad. Steinberg N, Siev-Ner I, Peleg S, Dar G, Masharawi Y, Hershkoviz I (2008). American Journal of Human Biology, 20 (3), 299-307. Viskić - Štalec N, Štalec J, Katić R, Podvorac Đ, Katović D (2007). Collegium Antropologicum, 31 (1), 259-66.